An approach towards optimal usage of immobilized sensor chips in surface plasmon resonance based biosensor - Honari, Parisa; Allaudin, Zeenathul Nazariah; Mohd Lila, Mohd Azmi; Mustafa, Nor Hidayah (Academic Journals, 2011)
In recent decades, there was a surge of interest in Surface Plasmon Resonance (SPR) biosensor based bimolecular interaction analysis. The unique characteristics of this technique made it possible to measure real time unlabelled bimolecular interactions with great sensitivity. However, the major challenge in SPR is providing the ability to re-use the surface of the chip. The main goal of this study was to address the problem faced in establishing an ideal regeneration condition and removing noncovalently bound analyt without disturbing ligand. Considering four different types of proteins including virus, hormone, cells and antibody, a comprehensive regeneration protocol for proteinprotein interaction was developed and compared with common regeneration methods. The presented protocol screened five multi-ingredient stock solutions that represented the five most common chemical properties such as acidic, basic, ionic, chelating and non-polar water soluble solvent solutions employed as regeneration agents. Upon three cycles of screening, it was found out that enveloped virus-antibody complexes could be effectively regenerated via a combination of acidic and chelating solution whilst non-enveloped viruses needed a basic solution for successful regeneration. Both insulin-antibody and cell-enveloped virus complexes could be detached efficiently using acidic solutions. Regenerations using non-polar water soluble solvents presented a harsh reaction, whilst ionic solutions were too mild. Thus, incomplete regeneration occurred. In summary, this study will serve as a platform of reference for multiple regenerations for a cluster of protein-protein complexes.